Women With Lesions Precursor of uterine cervical cancerand HPV: description socio-economicand demographic profile - Carvalho, Maria Cristina MP (2022)
Introduction: uterine cervix cancer has been identified as very frequent among Brazilian women that justifies the importance in identifying previously cervical cancer precursor lesions (LPCCU). The human papillomavirus (HPV) is the main agent for this type of cancer, being a serious problem in public health. It is important to know the socio-economic and demographic origins of women, which helps to reduce the number of cases of the disease. Objective:know and analyze women’s socio-economic and demographic profile with HPV and LPCCU. Methods: composed by 120 women diagnosed with LPCCU classified in Reproductive Age Group (IRG) and Group of Reproductive Age (GINR) in Service Cervical Pathology in a gynecology outpatient clinic of a Public University Federal of Rio de Janeiro in the Southeast. The study period was from February to June of 2008. A quantitative, descriptive research wa used. The data were highlighted in variables divided into economic characteristics, demographic and gynecologic obstetrics. The data were collected and analyzed by descriptive statistics by using single frequency (%). Results: the diagnosis of LPCCU ranged between the ages of 16 and 95 years old. GINR presented the highest percentage of women with LPCCU aged between 46 and 55. Family income in the two groups was highlighted by two minimum wages. The low level of education ranked high among the study subjects. Sexually transmitted disease was prevalent HPV infection. Conclusion: given the women’s socio-economic and demographic profile in the study, should emphasize the focus on educational activities and preventive strategies to infection by HPV, which will favor lower incidence of cervical cancer and LPCCU.